APLIKASI E-COMMERCE DENGAN FITUR TOP PRODUCT MENGGUNAKAN METODE PERCEPTRON (STUDI KASUS TOKO KAMERA) - Stefanus Alvin Hartono; Bagus Mulyawan; Janson Hendryli (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
The application e-commerce with top product feature using Perceptron method gives result making category of comment from user who gives some comment for product. The process of this method, first calculates the word weight with pre-processing that is using Term Frequency – Inverse Document Frequency (TF-IDF), then calculates comment using perceptron with weight it was specified by the training calculates.The test is done by using data from comments who user input at the product. Top procuct showed when comment was calculate with category from average good or bad reviews. The perceptron method calculate and predict the comment is inputed at the product.